145 Stress Echocardiography Demonstrates Excellent Feasibility, Safety and Diagnostic Accuracy in Patients with Significant Obesity: First Results from the Stress Ultrasonography in Morbid Obesity (SUMO) Study. (31st May 2014) - Shah, Benoy; Pabla, Jatinder S; Zacharias, Konstantinos; Balaji, Gothandaraman; Ramzy, Ihab; Alhajiri, Abdalla; Ahmed, Asrar; Gurunathan, Sothinathan; Elghamaz, Ahmed; Khattar, Rajdeep; Senior, Roxy
Abstract : Background: Significant obesity is an increasing global health problem. Obese individuals often have a clustering of cardiovascular risk factors such as hypertension, diabetes and dyslipidaemia. Thus, symptomatic patients often have a high pre-test probability of coronary artery disease (CAD) and are frequently referred for cardiac stress testing. These patients can provide significant technical challenges for imaging due to body habitus. The feasibility, safety and accuracy of stress echocardiography in patients with morbid obesity is unknown. Methods: In this prospective multi-centre study, height, weight, body mass index (BMI) and body surface area (BSA) of all patients clinically referred for SE were measured. For patients with BMI >35, patient demographics and SE test results were also collected. The feasibility of SE was defined as the ability to perform and complete the test, achieving interpretable images for all three coronary artery territories. Agreement with angiography findings in patients subsequently referred for cardiac catheterization was also evaluated. Results: Over an 11 month period across 3 hospitals, 2601 patients underwent SE, by 12 different operators, of whom 170 (6.5%) had BMI >35. Mean age was 59yrs, 44% were male and 25% had known CAD. Mean BMI was 39.5 and mean BSA was 2.2 m 2 . Dobutamine and exercise stress were performed in 60% and 40% respectively. Ultrasound contrast was used in 96% cases. There were no complications during the SE studies. SE demonstrated excellent feasibility, with a diagnostic test result achieved in 163/170 (96%) patients. Of the 7 patients with inconclusive SE, 2 were due to side-effects from dobutamine, 2 due to failure to reach target heart rate and 3 were due to poor image quality (thus just 3/170 [2%] due to poor image quality). Of 23 patients with inducible ischaemia, 19 proceeded to angiography and 17 had corresponding significant CAD (positive predictive value 89%). Conclusions: SE demonstrates excellent feasibility, safety and positive predictive value in real-world clinical practice in patients with morbid obesity. These results are clinically pertinent given the increasing proportion of such patients sent for non-invasive testing. Follow-up of this cohort to delineate event-free survival will reveal the accuracy of risk stratification of SE in this high-risk population.